INVESTIGATING ESP PRESENT-DAY THORNY SHORTCOMINGS AT IBN KHALDOUN UNIVERSITY OF TIARET IN ALGERIA - Benabed, Ammar (LLT Journal: A Journal on Language and Language Teaching, 2022)
The study investigates present-day situation of ESP teaching/ learning in four selected faculties at Ibn-Khaldun University namely science and technology, Electrical engineering, commercial sciences and Informatics and Mathematics. In these professional loci of pedagogical activity, most of the teachers who are in charge of ESP are EGP or ELT teachers. The ultimate objective of this investigation is to assess and/or measure the (in)effectiveness of the current system of teaching/learning English for specific purposes in the aforesaid faculties. To attain that, the four faculty deans and 8 teachers were interviewed, and 120 students were addressed a questionnaire. This would allow us to update and analyze a diversified set of data in terms of nurturing and structuring a rigorous educational engineering approach that results in a reasoned implementation. The results obtained revealed all stakeholders are fully aware of the importance of English language teaching, especially in the light of the current worldwide bets. The data also unveiled a set of thorny gaps characterizing the implementation of the subject such as less motivating syllabus content, teachers’ lack of theoretical insightful knowledge as regard ESP founding tenets supporting its teaching, the total absence of periodic training, lack of appropriate means and students’ indifference.